Overexpression of ∊-Protein Kinase C Enhances Nerve Growth Factor-induced Phosphorylation of Mitogen-activated Protein Kinases and Neurite Outgrowth - Bhupinder S. Hundle; Thomas McMahon; Jahan Dadgar; Robert O. Messing (1995)
Protein kinase C (PKC) activation enhances neurite outgrowth in several cell lines and primary neurons. The PKC isozymes that mediate this response are unknown. One clue to their identity has come from studies using PC12 cells treated with ethanol. In these cells, ethanol increases levels of δ-PKC and ∊-PKC and markedly enhances nerve growth factor (NGF)-induced neurite outgrowth and activation of mitogen-activated protein (MAP) kinases by a PKC-dependent mechanism. Since these findings suggest that δ-PKC or ∊-PKC can promote neural differentiation, we studied neurite outgrowth in stably transfected PC12 cell lines that overexpress these isozymes. Overexpression of ∊-PKC markedly increased NGF-induced neurite outgrowth. This effect was blocked by down-regulating PKC or by treating cells with the PKC inhibitor GF 109203X. In addition, overexpression of ∊-PKC enhanced NGF-induced phosphorylation of MAP kinases. In contrast, overexpression of δ-PKC did not alter responses to NGF. These results demonstrate that ∊-PKC promotes NGF-induced neurite outgrowth by enhancing NGF signal transduction. These findings suggest a role for ∊-PKC in neural differentiation and plasticity. Protein kinase C (PKC) activation enhances neurite outgrowth in several cell lines and primary neurons. The PKC isozymes that mediate this response are unknown. One clue to their identity has come from studies using PC12 cells treated with ethanol. In these cells, ethanol increases levels of δ-PKC and ∊-PKC and markedly enhances nerve growth factor (NGF)-induced neurite outgrowth and activation of mitogen-activated protein (MAP) kinases by a PKC-dependent mechanism. Since these findings suggest that δ-PKC or ∊-PKC can promote neural differentiation, we studied neurite outgrowth in stably transfected PC12 cell lines that overexpress these isozymes. Overexpression of ∊-PKC markedly increased NGF-induced neurite outgrowth. This effect was blocked by down-regulating PKC or by treating cells with the PKC inhibitor GF 109203X. In addition, overexpression of ∊-PKC enhanced NGF-induced phosphorylation of MAP kinases. In contrast, overexpression of δ-PKC did not alter responses to NGF. These results demonstrate that ∊-PKC promotes NGF-induced neurite outgrowth by enhancing NGF signal transduction. These findings suggest a role for ∊-PKC in neural differentiation and plasticity.